2021
DOI: 10.1007/s41465-021-00205-8
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Trainability and Transferability of Working-Memory Gating Policies

Abstract: Internal working memory (WM) gating control policies have been suggested to constitute a critical component of task-sets that can be learned and transferred to very similar task contexts (Bhandari and Badre (Cognition, 172, 33–43, 2018). Here, we attempt to expand these findings, examining whether such control policies can be also trained and transferred to other untrained cognitive control tasks, namely to task switching and AX-CPT. To this end, a context-processing WM task was used for training, allowing to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
2
2
0
Order By: Relevance
“…We have therefore demonstrated that both adults and 9-to 10-year-olds learn what approach they take to engage cognitive control from the repetition of task performance and so acquire knowledge of the temporal structure of task goal activation. In terms of adults, these findings are consistent with, and go beyond, previous studies (e.g., Bhandari & Badre, 2018;Sabah et al, 2021). Those studies demonstrated negative transfer effects using a working memory task, whereas we have extended this work by showing comparable results using the cued task-switching paradigm and the AX-CPT.…”
Section: Negative Transfer Effects Of Task Knowledgesupporting
confidence: 92%
See 2 more Smart Citations
“…We have therefore demonstrated that both adults and 9-to 10-year-olds learn what approach they take to engage cognitive control from the repetition of task performance and so acquire knowledge of the temporal structure of task goal activation. In terms of adults, these findings are consistent with, and go beyond, previous studies (e.g., Bhandari & Badre, 2018;Sabah et al, 2021). Those studies demonstrated negative transfer effects using a working memory task, whereas we have extended this work by showing comparable results using the cued task-switching paradigm and the AX-CPT.…”
Section: Negative Transfer Effects Of Task Knowledgesupporting
confidence: 92%
“…Consistent with previous studies (e.g., Bhandari & Badre, 2018;Sabah et al, 2021;Yanaoka et al, 2022) Experiments 3 and 4 provide further evidence that clarifies how learning a collective body of task knowledge positively affects cognitive control in a subsequent condition. In Experiment 4, we observed that school-aged children showed positive transfer effects on direct measures of using proactive/reactive control in the AX-CPT.…”
Section: Positive Transfer Effects Of Task Knowledgesupporting
confidence: 88%
See 1 more Smart Citation
“…We assume that this knowledge is essential in learning to engage proactive control. Recently, it has been established that adults learn when to activate a task goal in accordance with a task's temporal structure through the repetition of task experience (Bhandari & Badre, 2018, 2020; Bhandari et al., 2017; Sabah et al., 2021). Bhandari and Badre (2018) highlighted two control “policies” used in a working memory task, that is an input gating policy (first processing contextual information and then subsequently updating only items relevant to the context in working memory) and an output gating policy (accumulating all information and then subsequently processing contextual information and selecting only items relevant to the context).…”
Section: Introductionmentioning
confidence: 99%